Analysis of Smartphone Addiction With Anxiety in School-Aged Children - Erindia, Firnanda; Yusuf, Ah; Tristiana, RR Dian; Soleha, Umdatus (Universitas Airlangga, 2024)
Introduction: The increasing overuse of smartphones among children is a troubling addiction that affects both their physical well-being and mental health. It can lead to mood swings, withdrawal symptoms, emotional discomfort, and increased anxiety in social situations. This study aimed to analyze the correlation between smartphone addiction and anxiety levels among students at Pawyatan Daha Elementary School in Kediri, East Java. Methods: This study utilized a cross-sectional design with a simple random sampling method involving 154 students from Pawyatan Daha Elementary School in Kediri, East Java. Data collection occurred from November to December 2022. The independent variable in this research was smartphone addiction, assessed using the Smartphone Addiction Risk Children Questionnaire (SARCQ). In contrast, the dependent variable was anxiety, measured by the Revised Child Anxiety and Depression Scale (RCADS). Data analysis was conducted using Spearman's rho test with a significance level of α = 0.05. Result: The findings indicated that a majority of respondents (77.3%) fell into the high category of smartphone addiction, while 52.6% were identified as experiencing general anxiety disorders. Statistical analysis revealed a significant correlation, with a p-value of 0.001 (p < 0.005) and an R-value of 0.330. Conclusions: The study concludes that there is a correlation between smartphone addiction and anxiety among school-aged children. Parents must supervise their children's smartphone usage to foster character development and prevent addictive behaviors. Additionally, nurses can play a crucial role as counselors by providing regular counseling services in elementary schools to mitigate smartphone addiction.